2016
DOI: 10.1111/ene.13030
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum vascular endothelial growth factor levels and cerebral microbleeds in patients with Alzheimer's disease

Abstract: Serum VEGF levels are associated with the presence of CMBs in patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The seventh study demonstrated increased vascular endothelial growth factor levels in serum of AD patients with CMBs ( n = 47) vs. AD patients without CMBs ( n = 99) ( 48 ). The eighth study showed increased BBB dysfunction in the form of an increased CSF/serum albumin ratio in patients with cognitive decline with CMBs ( n = 15) compared with patients with cognitive decline but no CMBs ( n = 13) ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The seventh study demonstrated increased vascular endothelial growth factor levels in serum of AD patients with CMBs ( n = 47) vs. AD patients without CMBs ( n = 99) ( 48 ). The eighth study showed increased BBB dysfunction in the form of an increased CSF/serum albumin ratio in patients with cognitive decline with CMBs ( n = 15) compared with patients with cognitive decline but no CMBs ( n = 13) ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy may be due, in part, to the fact that there is mixed epidemiological evidence of risk and resilience when measuring VEGF. High levels of serum VEGF have been associated with an increased risk of stroke (Pikula et al, 2013) and more frequent cerebral microbleeds among individuals with Alzheimer's disease (Zhang et al, 2016), while CSF VEGF levels have been reported to be higher (Tarkowski et al, 2002), lower (Guo, Alexopoulos, & Perneczky, 2013), and equivalent (Blasko et al, 2006) among individuals with AD compared to controls. Perhaps VEGF-related genes like PROK1 will provide clues to help unravel the complex associations among VEGF, cerebrovascular disease, and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, oncological studies have shown that VEGF may serve as a serum biomarker for angiogenic processes that are associated with the progression of different forms of cancer, such as colorectal tumors [ 24 ]. In AD, one study showed increased serum VEGF levels in AD patients of microbleeds whereas another study demonstrates [ 25 ] lower levels of serum VEGF in patients compared to age-matched controls [ 26 ], illustrating its suitability as a potential biomarker for AD.…”
Section: Introductionmentioning
confidence: 99%